Total biocatalytic synthesis of capsaicinoids using ferulic acid: a versatile two-step strategy for natural product diversification - Khobragade, Taresh P.; Giri, Pritam; Patil, Mahesh D.; Joo, Sangwoo; Cho, Sunga; Kim, Yechan; Ghosh, Rohan; Jeong, Sanghun; Maeng, Minyeong; Song, Min-Ho; Park, Jeong-Min; Lee, Eun Ho; et al. (Angewandte Chemie-International Edition, 2025)
The wide-ranging application of capsaicinoids, the active compounds in chili peppers, has driven increasing interest in the development of sustainable production strategies. However, capsaicinoid synthesis remains a challenge. The objective of this pioneering study is to report the total biocatalytic synthesis of structurally diverse capsaicinoids from bio-based ferulic acids. An X-ray crystallographic study elucidated the structural basis for the exceptional potential of a novel transaminase from Phaeobacter porticola (PPTA) to transform the highest ever reported concentration of vanillin (100-200 mM) to vanillylamine, with >99% conversion and modest conversion ranging from 48% to 79% for 300 to 500 mM substrate. Using PPTA in tandem with phenolic acid decarboxylase (PAD) and aromatic dioxygenase (ADO) further enabled the direct synthesis of vanillylamine from ferulic acid with >99% conversion. Furthermore, the integration of a multi-enzymatic cascade with carboxylic acid reductases (CARs) successfully synthesized structurally diverse capsaicinoids via amide bond formation between vanillylamine and free fatty acids, with excellent conversions ranging from 72% to >88%. A 50-mM enzymatic reaction afforded 95% and 80% conversion of vanillylamine and capsaicin, respectively.
Keywords: Capsaicinoids; Carboxylic acid reductase; Transaminase; Vanillylamine